2013
DOI: 10.1063/1.4821161
|View full text |Cite
|
Sign up to set email alerts
|

Ion selection of charge-modified large nanopores in a graphene sheet

Abstract: Water desalination becomes an increasingly important approach for clean water supply to meet the rapidly growing demand of population boost, industrialization, and urbanization. The main challenge in current desalination technologies lies in the reduction of energy consumption and economic costs. Here, we propose to use charged nanopores drilled in a graphene sheet as ion exchange membranes to promote the efficiency and capacity of desalination systems. Using molecular dynamics simulations, we investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 57 publications
3
70
0
Order By: Relevance
“…The observed selectivity is likely due to electrostatic interactions with the negative charges from the functional groups terminating the edge of the pore as predicted by recent simulations. 2,3,8 These measurements demonstrate that the nucleated defects were initially impermeable to both ions, but gradually became permeable to the potassium and chloride ions after exposure to the etchant. As the etching progressed the membrane potential slowly decayed to zero, indicating loss of selectivity between the potassium and chloride ions.…”
Section: Table Of Contents Graphicmentioning
confidence: 88%
See 1 more Smart Citation
“…The observed selectivity is likely due to electrostatic interactions with the negative charges from the functional groups terminating the edge of the pore as predicted by recent simulations. 2,3,8 These measurements demonstrate that the nucleated defects were initially impermeable to both ions, but gradually became permeable to the potassium and chloride ions after exposure to the etchant. As the etching progressed the membrane potential slowly decayed to zero, indicating loss of selectivity between the potassium and chloride ions.…”
Section: Table Of Contents Graphicmentioning
confidence: 88%
“…Regardless, stabilization of pore size allows for a tighter distribution of pore diameters than that possible in case of a linear growth rate, and also results in subnanometer pores that are predicted to exhibit the selectivity required for nanofiltration, desalination, and gas separation. [1][2][3][4][5] To investigate transport across the created pores, we fabricated a graphene composite membrane (GCM) by direct transfer of graphene from copper foil 36 to a polycarbonate track etch (PCTE) membrane support 24 ( Fig. 5a and Fig.…”
Section: Table Of Contents Graphicmentioning
confidence: 99%
“…34 In addition to size exclusion effect, the nanopore chemistry and thus the electrical charge of the nanopore edge also affect ion rejection. 12 As shown by molecular dynamics simulations, 35 the presence of negatively charged functional groups at the nanopore edge hampers the flux of negative ions (Cl − ), thereby enhancing the salt rejection efficiency. The fourth mechanism, that is, subtler pore/solute interactions, is directly correlated to the nanopore morphology and has been mainly studied regarding biological membranes rather than graphene membranes.…”
Section: Graphene Desalination Membranesmentioning
confidence: 99%
“…Theoretical analyses showed that higher ion exclusion rather than a change in the permeability of the membrane was obtained when specific terminating groups were present [40,53]. MD simulations also showed selectivity of NPG against salt rejection, since it is permeable to specific solvated ions and impermeable to others [54,55]. Finally, MD simulations evidenced that the water permeability of NPG membranes also depended on the density of nanopores per unit area [39].…”
Section: Geofluidsmentioning
confidence: 85%
“…For example, the critical nanopore diameter for rejecting NaCl was estimated to be in the range 0.6-0.8 nm [56]. Another important mechanism is charge repulsion between salt ions and the chemical groups at pore edges [55,57]. Finally, the rejection of salts is also favored by limiting the number of physical configurations, that is, geometrical orientations that would allow for salt ions to pass through the nanopores.…”
Section: Geofluidsmentioning
confidence: 99%